PESANTREN TANFIDZIYAH: Analisis Pengembangan Kurikulum di PP. Al-Muayyad Windan Sukoharjo - Anas Aijudin (Badan Litbang dan Diklat Kementerian Agama RI, 2009)
AbstractThis study is based on the fact that almost all traditional Islamic boarding schools prepare their students to become expert of religious instructions. Only a few preparing their students, in addition to master the â€˜yellow bookâ€™ tradition, on how to apply it among the communities also. The curriculum of Al-Muayyad Windan Islamic boarding school, Sukoharjo is formulated to mature students in both categories above. The funding of study informs that Al-Muayyad Windan Islamic boarding school has a Tanfidziah model with an integrated curriculum, i.e. the mastering on religious texts derived from â€˜yellow booksâ€™ which enables the students to master religious science (mutafaq addin), capable at the implementation level, so the students having the capacity to be â€œtune inâ€ in the people empowerment.